The Annual of The NORTH DAKOTA Agricultural College 1914 - Ye College Chronicle - North Dakota Agricultural College (Fargo, N.D.); Fargo (N.D.); (North Dakota State University Library, University Archives;, 1914)
THE 1914 Agassiz 268 Ye College Chronicle - Continued Friday January 24 Musical Extravaganza-some show, eh! Major King takes a shot at the airship, but it fails to descend - result, cussing among the Black Squad. A. C. 29, Wahpeton Science 18. Ethel gets balled out in Dutch. Saturday January 25 Freshies have an exciting sleigh-ride. Juniors (?) defeat Hillsboro 52 to 27. Sunday January 26 Everybody at Ceres invites somebody else to dinner. Monday January 27 Co. A tries to get frisky with the cadet officers, but are soon squelched, humbled and mortified. Edna and Julia make their Wedding-cake. Tuesday January 28 Juniors work night and day on the apple blossoms. Miss. Taylor somewhat peeved with her class in Textiles. Wednesday January 29 Good morning, have you got the measles? Thursday January 30 Day of Prayer. Juniors start decorating the armory. Several of the more aristocratic members of the class respond to urgent phone calls in the coach's office in the evening. Junior girls plan on starting a Keeley Cure Institute. Friday January 31 Juniors skip classes all day and labor on the prom; even Ogaard declares it to be the most successful and beautiful prom ever held. Nuff sed. Hildur stings her swain and goes to the prom with another maiden's jigger. FEBRUARY Saturday February 1 The morning after the night before. Curses, we go in the hole. Ogaard manages to think up some criticism of the prom. Sunday February 2 Marion and Dean so absorbed that they go by their church and have to walk back. Monday February 3 Tag Day for the Student Special. Young and verdant orators turned loose in chapel. Band makes a hit with its syncopated marches. The Registrar passes around the cigars. Tuesday February 4 Rube deports the "Cooperstown jane" and freezes his ears on the way to the train. Rube decides to lead the simple life for a while. Eulalia afraid that Walter will get the measles because he sits next to the nurse at Ceres. Wednesday February 5 Arctic zephyrs waft away Ruby's priceless chemistry notes - Ruby says "darn." Pooley gives Dr. Batt a severe jolt in class. Grace sick, Bobby looks disconsolate. Viewbooks; 27 x 20 cm. Title taken from cover of book